Quality of Life in Diabetic Patients: The Predicting Role of Personal Resources - Mohammad Hossein Kaveh; Somayeh Zare; Leila Ghahremani; Mahin Nazari (Shiraz University of Medical Sciences, 2018)
Background: Diabetes control is highly self-care and emotional complications and mental stress play an important role in controlling blood sugar in diabetes, and these factors affect the quality of life of people with diabetes. The aim of this study was to determine the predicting role of personal resources for quality of life in diabetic patients. Methods: This was a cross-sectional study done in 2017. The population of this study was all diabetic patients referred to Shahid Motahari, Imam Reza (AS) and Nader Kazemi clinics in Shiraz in 1396. A total of 198 patients were selected by simple random sampling method. Quality of life, optimism, self-efficacy of diabetic and resiliency questionnaires were used for data collection. Data were analyzed by SPSS software version 19 using Pearson correlation and multivariate regression. Results: Findings showed that resiliency, self-efficacy and optimism had a positive and significant relationship with the quality of life of patients with diabetes. In a prediction model, self-efficacy and resiliency could predict 19% of the quality of life changes in patients with type 2 diabetes (p <0.05). The findings of this study showed that self-efficacy and resilience variables predicted the quality of life of patients, but optimism had no predictive power. Conclusion: The results of this study showed that increased self-efficacy and resiliency lead to increased quality of life in diabetic patients. This may help the patients to cope with problems and excitement and is effective in planning interventions for diabetics.